Impacts of Stepwise Aging/Freezing Process and Repeated Freezing on Meat Quality, Physicochemical and Biochemical Properties, and Sensory Attributes of Beef Loins - Brad Kim; Dong-Jin Shin; Jinkyu Seo; Madison Romanyk; Saud Ur Rehman (Meat and Muscle Biology)
The study aimed to investigate the impact of aging durations prior to and after repeated freezing/thawing cycles on the quality attributes of beef loins. At 2 d postmortem, paired beef loins from 30 carcasses were divided into aging groups (0, 2, 3, and 4 weeks at 2°C) named A0, A2, A3, and A4, respectively. Sections from each group were taken as never-frozen samples (F0T). The 4-week aged subsections were stored for an extra week as long-term aged-only controls (A5). The remaining portions were frozen for 1 to 5 weeks, creating a total aging/freezing cycle of 5 weeks. After the initial freezing periods, samples were thawed and collected as aged/frozen samples (F5T, F3T, F2T, F1T). The remaining portions were frozen again for 5 weeks and thawed as repeated frozen/thawed samples (F5T × 2, F3T × 2, F2T × 2, F1T × 2). Aging significantly reduced freeze/thaw losses, with the least losses observed in 4-week-aged, one-time frozen samples (A4F1T; P < 0.05). Repeatedly frozen samples exhibited lower losses compared to one-time frozen samples. Cooking loss was not different between never-frozen and aged/frozen samples (P > 0.05). In non-aged samples, instrumental tenderness significantly decreased with repeated freezing (A0F5T × 2), comparable to 5-week aged-only (never-frozen) samples (A5F0T; P > 0.05). The myofibrillar fragmentation index increased with aging coupled with freezing (P < 0.05). Lipid oxidation was increased in 4-week-aged, repeatedly frozen samples (A4F1T × 2, P < 0.05). Carbonyl content increased with aging and freezing processes (P < 0.05). Repeated freezing adversely affected display color stability compared to never-frozen samples. The consumer panel (n = 90) found no differences in eating quality attributes (P > 0.05), regarding liking of tenderness, flavor, juiciness, and overall liking between the aging/freezing samples. The results of the study suggest that stepwise aging/freezing can provide protective effects against moisture loss during freezing and repeatedly frozen/ thawed processes, likely due to increases in muscle fragmentation. Stepwise aging/freezing can be a viable approach for the meat industry for the consistent supply of frozen beef with quality equivalent to fresh meat.